Consumer Evaluation of Digital Health Information Credibility in Online Consultation Decision-Making - Muhammad Hilmi Labibunnajah; Yusuf Kusuma Dewa; Nanda Adi Utami (Indonesian Economic Review, 2026)
The rapid​ development of digital technology has led people to increasingly rely on the internet as an initial source of health information before making medical decisions. However, the varying quality of digital health information requires consumers to evaluate its credibility before using it as a basis for decision-making, including decisions to use online health consultation services. This study aims to understand how consumers evaluate the credibility of digital health information and how this evaluation process influences their decisions to use telemedicine services. This research employed a qualitative approach with a phenomenological perspective. Data were collected through in- depth interviews with participants who had searched for health information online and had experience using online medical consultation services. Participants were selected purposively, and the number of participants was determined based on the principle of data saturation. The data were analyzed using thematic analysis to identify patterns of experience and meaning constructed by participants when assessing information credibility. The findings reveal that credibility evaluation is a complex and contextual process influenced by personal experiences and emotional conditions. Consumers assess credibility based on source authority, consistency of information across sources, and prior usage experiences. Emotions such as anxiety also shape how individuals interpret information. Information perceived as credible increases confidence and reduced perceived risk, thereby encouraging the decision to use online consultation services. conversely, information perceived as less credible leads to confusion and delays in decision-making. These findings highlights that the credibility of digital health information serves as a psychological foundation for building trust in telemedicine services.